Expected Medium- and Long-Term Impact of the COVID-19 Outbreak in Oncology. (2021) - Onesti, Concetta Elisa; Tagliamento, Marco; Curigliano, Giuseppe; Harbeck, Nadia; Bartsch, Rupert; Wildiers, Hans; Tjan-Heijnen, Vivianne; Martin, Miguel; Rottey, Sylvie; Generali, Daniele; Campone, Mario; Cristofanilli, Massimo; et al.
Abstract : PURPOSE: The COVID-19 pandemic has affected healthcare systems globally, leading to reorganization of medical activities. We performed an international survey aimed to investigate the medium- and long-term impact on oncology units. MATERIALS AND METHODS: An 82-item survey was distributed from June 17 to July 14, 2020 among medical oncologists worldwide. RESULTS: One hundred nine medical oncologists from 18 countries in Europe (n = 93), United States (n = 5), and Latin America (n = 11) answered the survey. A systematic tracing of COVID-19–positive patients was continued in the postacute phase by 77.1% of the centers; 64.2% of the respondents participated in a local registry and 56% in international or national registries of infected patients. Treatment adaptations were introduced, and surgery was the most affected modality being delayed or canceled in more than 10% of patients in 34% of the centers, whereas early cessation of palliative treatment was reported in 32.1% of the centers; 64.2% of respondents reported paying attention to avoid undertreatments. The use of telemedicine has been largely increased. Similarly, virtual tools are increasingly used particularly for medical education and international or national or multidisciplinary meetings. 60.6% of the participants reduced clinical activity, and 28.4% compensated by increasing their research activity. Significant reduction of clinical trial activities is expected in 37% of centers this year. The well-being of healthcare staff would not recover by the end of the year according to 18% of the participants. CONCLUSION: The COVID-19 outbreak has had a major impact on oncologic activity, which will persist in the future, irrespective of geographical areas.